Cervical cesarean damage as a growing clinical problem: The association between in-labour cesarean section and recurrent preterm birth in subsequent pregnancies. - Laura van der Krogt; Andrew Shennan (PLoS Medicine)
Increasing evidence supports an association between in-labour cesarean section and recurrent preterm birth in subsequent pregnancies. This clinically challenging problem may be caused by cervical damage at the time of in-labour cesarean section.